Ripple across the water 95. (Watari : Watari museum of contemporary art, 1995)
Acconci, Vito ; Bacon, Francis ; Bade, David ; Balka, Miroslaw ; Barney, Matthew ; Biefer, Marcel ; Zgraggen, Beat ; Cabrita Reis, Pedro ; Cai Guo-Qiang ; de Cordier, Thierry ; Deleu, Luc ; Diamond, Jessica ; Dumas, Marlene ; Fabre, Jan ; Herold, Georg ; Hirakawa, Noritoshi ; Hosono, Haruomi ; Huang Yong Ping ; Kapoor, Anish ; Kawamata, Tadashi ; Lebret, Patrick ; Miyajima, Tatsuo ; Müller, Piotr ; Muñoz, Juan ; Nauman, Bruce ; Parreno, Philippe ; Pistoletto, Michelangelo ; Preesman, Avery ; Prum, Antoine ; Quinn, Mark ; Rabinowitch, Royden ; Ramette, Philippe ; Rhoades, Jason ; Ross, Michael ; Santino, Peter ; Sone Yutaka ; West, Franz ; Wisniewski, Jeffrey ; Woodrow, Bill
Ripple across the Water '95, Watari-Um, The Watari Museum of Contemporary Art, Tokyo, 02.09.1995 - 01.10.1995
kunstcatalogus